1991
DOI: 10.1177/0011000091192013
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian Career Development, Work Behavior, and Vocational Counseling

Abstract: Women 's career development has recently been a popular topic in counseling psychology, for both theoretical and empirical work This article extends that line of inquiry to address the unique career development issues of lesbians. The available literature on lesbians and work is reviewed, and parallels are drawn between the work experiences of lesbians, nonlesbian women, and other minority status groups. Three models of career development in women (Astin, 1985; Farmer, 1985; Gottfredson, 1981) are presented, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 23 publications
2
100
0
Order By: Relevance
“…It seems that many GLB students recognize that similar role models will serve important functions that heterosexual career role models may be unable to serve. Thus, consistent with social learning theory (Bandura, 1977), they may be looking to role models perceived as similar to themselves to challenge stereotypes, help them anticipate the consequences of being out in the workplace, and help them learn how to cope with such consequences (Croteau & Thiel, 1993;Elliott, 1993;Ettinger et aI., 1990;Hetherington & Orzek, 1989;Morgan & Brown, 1991). On the other hand, the GLB students in this study reported significantly less support/guidance from others when they made academic and career decisions than did the heterosexual sample.…”
Section: Discussionmentioning
confidence: 95%
“…It seems that many GLB students recognize that similar role models will serve important functions that heterosexual career role models may be unable to serve. Thus, consistent with social learning theory (Bandura, 1977), they may be looking to role models perceived as similar to themselves to challenge stereotypes, help them anticipate the consequences of being out in the workplace, and help them learn how to cope with such consequences (Croteau & Thiel, 1993;Elliott, 1993;Ettinger et aI., 1990;Hetherington & Orzek, 1989;Morgan & Brown, 1991). On the other hand, the GLB students in this study reported significantly less support/guidance from others when they made academic and career decisions than did the heterosexual sample.…”
Section: Discussionmentioning
confidence: 95%
“…The original 20-item Affirmative Behaviors with GLB Clients subscale asked participants to rate statements that describe their behaviors with clients expressing gay, lesbian, and bisexual career concerns. Articles that addressed the career concerns of gay, lesbian, and bisexual individuals (i.e., Croteau & Thiel, 1993;Elliott, 1993;Hetherington, Hillerbrand, & Etringer, 1989;Morgan & Brown, 1991) were consulted and a list of recommended culturally affirmative counselor behaviors for working with gay, lesbian, and bisexual clients was generated. Item development was guided by this comprehensive list of behaviors.…”
Section: Instrumentsmentioning
confidence: 99%
“…Making the decision to disclose sexual orientation is often fraught with damaging consequences, yet many researchers (e.g., Croteau & Hedstrom, 1993;Elliott, 1993;Fassinger, 1991Fassinger, ,1996Morgan & Brown, 1991) have acknowledged the toll that is taken on the mental health oflesbians who exert the energy necessary to maintain secrecy. Conversely, by coming out, lesbians may open themselves up to discrimination and harassment, which can lead to constant fear and anxiety (Gelwick, 1984).…”
Section: Reinforcement Valuesmentioning
confidence: 99%
“…Counselors should have a basic understanding of the process of sexual identity formation to better understand the client and to understand its impact on the client's work, work relationships, reinforcement values, satisfaction, and other important areas of interface with the work environment (Boatwright et a!., 1996;Croteau & Hedstrom, 1993;Day & Schoenrade, 1997;Elliott, 1993;Fassinger, 1996;Morgan & Brown, 1991). The counselor should be prepared to assist the client in her quest to weigh the values of disclosure and nondisclosure.…”
Section: Implications For Counselorsmentioning
confidence: 99%